SIFAT-SIFAT MEKANIK MATERIAL KOMPOSIT BERBAHAN DASAR FLY ASH DAN PASIR HALUS - La Ode Muhaimin; Minson Simatupang (Dinamika : Jurnal Ilmiah Teknik Mesin, 2020)
Soil stabilization using fly ash is an attractive alternative to be developed. Besides reducing industrial waste, it is also economical in terms of costs. With the presence of water, the lime contained in fly ash would be decomposed and undergone a cementation process and a pozolan reaction which would bind the sand grains. In this study, the effect of fly ash content and curing period on the amount of compressive strength and shear strength was observed using an unconfined compressive and direct shear test, respectively. The stress-strain relationships due to shear loads between sand without fly ash and sand with fly ash were compared to see an increase in shear strength due to the addition of fly ash. The results show that the unconfined compressive strength and shear strength of the composite material increase with the addition of fly ash and curing period. But the opposite happened in compressive strain. It was confirmed that the strain to achieve maximum compressive strength decreased with increasing fly ash content and curing period. The fly ash bond was getting brittle with the increasing compressive strength of the composite material made from fly ash and fine sand.